Weyses klavermusik - Busk, Gorm (Danish Yearbook of Musicology, 1996)
Weyse’s Piano Music Though the Danish composer Christoph Ernst Friedrich Weyse (1774-1842) is mainly known for his vocal music, he was also a distinguished pianist and organist. Of his piano works, which are now to be published, the earliest are found in two volumes of Jugendarbeiten 1790-1794. They consist of smaller pieces, fugues and a fantasia, but first and foremost they include four sonatas and eight movements in sonata form. Weyse composed 19 such sonata form movements in all and was the first composer to publish this type of piano music under the name of Allegri di bravura. Two collections of six and four allegri and a volume with Vermischte Compositionen with some more sonatas were issued about 1800. After these works, written in the classical style, Weyse gave up composing for the piano. However, inspired by the piano virtuoso and composer Ignaz Moscheles, who visited Copenhagen in 1829, he wrote a large-scale Allegro di bravura for him and 12 studies in a different, wholly romantic idiom. Weyses output for piano thus shows considerable stylistic variety, but nevertheless is very personal and of the best in Danish music.